Tools and Algorithms for the Construction and Analysis of Systems: 24th International Conference, TACAS 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings, Part I - Beyer, Dirk; Huisman, Marieke (Theoretical Computer Science and General Issues, 2018)
authentication; computer science; computer software selection and evaluation; cryptography; data privacy; formal logic; formal methods; formal specification; internet; privacy; program compilers; programming languages; security systems; semantics; separation logic; software engineering; verification; world wide web